Free Volatile Compounds of cv. Pedro Giménez (Vitis vinifera L.) White Grape Must Grown in San Juan, Argentina - Maturano, Y.P.; Nally, M.C.; Assof, M.V.; Toro, M.E.; Castellanos de Figueroa, L.I.; Jofré, V.P.; Vazquez, F. (South African Journal of Enology and Viticulture, 2018)
The free aromatic composition of must from Pedro Giménez grapes, grown in San Juan, Argentina, was characterised. Samples from the vintages of 2008 and 2009 were analysed by gas chromatography–mass spectrometry–solid phase microextraction (GC–MS–SPME). Higher alcohols, terpenes, C13-norisoprenoids, esters, aldehydes and ketones were quantified. The calculation of the odour activity values (OAVs) revealed that β-damascenone, α-ionone, β-linalool, geraniol, ethyl butanoate, hexanoate and octanoate were the most prevalent aroma-active compounds of the grape variety. However, the remaining 42 aromatic compounds that registered OAVs less than 1 could potentially contribute to the flavour of Pedro Giménez grapes. The measured monoterpene levels indicate that the Pedro Giménez grape can be considered a neutral variety. This is the first report describing the main potential free aroma contributors of Pedro Giménez grapes in two consecutive years.